Antihypertensive And Vasodilatory Effects Of Vernonia Amygdalina And Swietenia Macrophylla Extracts - Ch’ng, Yung Sing (2017)
In Malaysia, hypertension is an increasingly important medical and public health issue and there is an imminent need to decrease its prevalence. In this study, the local herbs in Malaysia such as Clinacanthus nutans Lindau, Strobilanthes cripus, Murdannia bacteata, Elephantopus scaber Linn., Pereskia bleo, Pereskia grandifolia Haw., Vernonia amygdalina, and Swietenia macrophylla King seeds were selected and their extracts (water extracts, 50% ethanol extracts, and 95 % ethanol extracts) underwent preliminary testing to screen for their antihypertensive activities and their vasorelaxation. The results showed that the seeds of Swietenia macrophylla King has the highest potential in vasorelaxation, followed by Vernonia amygdalina. This study found that, crude VAE and SM50, which contain multiple chemical components, exhibited a stronger vasorelaxant effect on isolated aortic rings due to their possible involvement of multiple mechanisms.